Tribology as emerging science for warm mix technology: A review - Wagh V.P.; Saboo N.; Gupta A. (My University, 2025)
Tribology is the most common science used for studying the interaction between two surfaces separated by a lubricant. It is an interdisciplinary science that deals with friction, wear, and lubrication. The reach of tribology has been extending to various domains, and one of such domains is the pavement industry. Tribology-related research activities in pavement areas have shown immense progress during the last two decades. Recently it has been used for the assessment of warm mix asphalt (WMA) technology which offers a reduction in production temperature by 20–50 °C. WMA offers mixing and densification of asphalt mixes at lower temperatures due to a reduction in friction at the contact zone between aggregate particles in relative motion. The lubricating behaviour of asphalt binder between mineral aggregates in relative motion can be assessed through tribology. This behaviour is generally quantified in terms of coefficient of friction (CoF) and evaluated using the standard Stribeck curve. Various test geometries have been used for CoF measurement. Tribological characterisation is generally affected by the interacting surfaces features. Surface roughness is one such characteristic parameter that affects the CoF. This paper gives an overview of the studies regarding the tribological assessment of asphalt binders. Tribological tests, geometries, and test procedures adopted for roughness characterisation are elaborated in this study. This review highlights the influence of WMA technology and test parameters on CoF. The review also focuses on the characterisation of interacting surfaces using various surface roughness parameters. Critical gaps in existing studies and the need for further research in this area are identified. © 2022 Elsevier Ltd